Zastosowanie technologii big data w e-biznesie - Gamrot, Michał (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
Big data, defined as a process of storing, transforming and analyzing large volumes of data, is one of the most discussed issues in e-commerce. By gathering large quantities of data about their customers, e-commerce practitioners can gain valuable insights regarding (1) the reasons of why people are making purchases and (2) maximum prices they are willing to pay for certain goods, in order to maximize profit margins. By analyzing customer’s behavior it’s also possible to (3) identify patterns that indicate fraud, which in turn might greatly reduce costs and risks of e-commerce business.Big data also has its limitations. Storing, transforming and analyzing large quantities of data is costly and because big data is still a relatively new technology, the supply of skilled professionals is low. Big data poses also some difficult methodological concerns, i.e. whether or not more data always leads to better insights and whether online data shouldn’t be supplemented by external, more traditional sources. The paper mentions also the issue of privacy, observing that it’s one of the main factors affecting success of big data technologies in the future.